Clinical researchChanges in transforming growth factor β and its receptors’ mRNA expression in monocytes from patients with acute coronary syndromes - Kulach, Andrzej; Dabek, Jozefa; Wilczok, Tadeusz; Gasior, Zbigniew (Archives of Medical Science, 2010)
Introduction: Transforming growth factor β (TGF-β) is thought to be a vasoprotective cytokine. Numerous reports confirm its significance in blood and plaques. There is, however, a lack of information on the molecular mechanisms involving TGF-β in circulating inflammatory cells in atherogenesis. The aim of the study was to assess gene expression of TGF-β and its receptors in monocytes from patients with acute coronary syndromes (ACS) and the effect of standard treatment on the studied genes. Material and methods : The study was carried out in 32 patients with ACS and 15 healthy subjects. Gene expression of TGF-β and receptors TGF-βRI and TGF-βRII was evaluated on day 1 and 5 in the study group and once in controls. The number of mRNA copies isolated from monocytes was assessed by QRT-PCR. Results: Monocytes of ACS patients showed slightly elevated transcriptional activity of TGF-β1 and its receptors RI and RII genes (0.29 ±0.043 vs. 0.08 ±0.020, p = 0.05; 0.071 ±0.022 vs. 0.036 ±0.023, p < 0.05; 0.134 ±0.020 vs. 0.048 ±0.016, p < 0.05, respectively). After 5-day standard treatment modest reduction of TGF-βRI expression was observed. The studied genes’ expression was unrelated to ejection fraction, myocardial necrosis markers, GRACE score, time from the onset of pain to percutaneous coronary intervention and angiographic findings. Among risk factors family history of CAD was associated with increased TGF-βRI expression. Moreover, the presence of 4 or more classic risk factors correlated with higher TGF-βRI expression. Conclusions: Monocytes of ACS patients demonstrate overexpression of TGF-β1 and its receptors’ genes. Five-day standard treatment downregulated the TGF-βRI gene but did not affect TGF-β1 and TGF-βRII.